FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN KADER KESEHATAN TENTANG THALASSAEMIA DI KECAMATAN SUMBANG KABUPATEN BANYUMAS - Wardani, Nur Indah Indah; Sri Rejeki, Dwi Sarwani; Masfiah, Siti (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACT The number of thalassaemia patients in  Banyumas regency continues to increas every year. Indonesian Thalassaemia Foundation or YTI (Yayasan Thalassaemia Indonesia) in Banyumas records that from 2009 until 2012  the number of patients increase from 44 to 235 patients. Prevention is necessary to decrease the number of thalassaemia patients by health volunteer?s role as an enabling factor to change public behavior. It will happen if only the health volunteer has the sufficient level of knowledge, especially about thalassaemia. This research to determine about factors related to health volunteer?s level of knowledge about thalassaemia in Sumbang district  Banyumas regency. This research is an analytic research with cross sectional design. The population of this research is all of health volunteers (76 people) in Kecamatan Sumbang. The sample is 30 health volunteers that selected with purposive sampling method. The data that used a primer data that collected by questionnaire and analyzed in univariate and bivariate analysis with chi square test. Based on bivariate analysis result, there are a relation between interest (p=0,014) and being active as a health volunteer (p=0,034) with the level of knowledge about thalassaemia. There are no relation between age, education, occupation, income, experience, information exposure and period of service with the level of knowledge about thalassaemia. Suggestion for health volunteers is active disseminating information to the public about thalassaemia. Key words                : Health Volunteer, Knowledge, Thalassaemia  Kesmasindo, Volume 6, (3) Januari 2014, Hal. 194-206